Pectus cross bars increase hospital readmission rates due to serous pleural effusion - BEKİROĞLU, GÜLNAZ NURAL; YÜKSEL, MUSTAFA (SPRINGER JAPAN KK, 2022)
Objective Pectus Excavatum's (PE) surgical treatment should be patient specific. In this article, we aimed to compare parallel and cross bar variations of the Nuss method and analyze if there is any difference in results. Methods In this study, a total of 891 patients treated with the Nuss method between August 2005 and February 2018 were considered. These were retrieved from a prospectively recorded PE database. Of these, 276 double-bar patients were included in the study. Patients with parallel bars (225 cases) and patients with crossed bars (51 cases) were compared in terms of age, gender, symmetry, family history, additional anomalies, mean operation time, postoperative hospital stay (days) and hospital readmission rate. Results The mean age was measured at 20.7 for parallel bar patients and 20.1 for crossed bars patients. There was no statistically significant difference in terms of age, gender, and mean operation time between two groups. On the other hand, statistical significance was found between two groups when analyzing the deformities' symmetry, patients' family history and additional anomalies. The statistically significant difference of postoperative hospital stay between two groups is clinically negligible. Postoperative hospital readmission rates due to serous pleural effusion were found to be significantly increased in patients with crossed bars (p < 0.001). Conclusion While pleural effusion requiring readmission was statistically more frequent in cross bars, in centers where thoracentesis can be managed, Nuss method can still be applied safely, even in cases with difficult, complex deformities.
Keywords: Pectus excavatum; Chest wall deformity; Pleural effusion; MIRPE; Nuss procedure; Cross bars; MINIMALLY INVASIVE REPAIR; NUSS PROCEDURE; PULMONARY-FUNCTION; EXCAVATUM; COMPLICATIONS; MULTICENTER; EXPERIENCE